Transforming Physics Classrooms through Art Integrated Learning: A Survey Study - Pal, Mamta (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Present 21st century demands the learners to apply the knowledge gained I the classrooms to solve real problems which are impossible if the students do not understand the concepts in physics. The gravity of the situation is exacerbated given the wrong pedagogies adopted in the classrooms. Such pedagogies kill the interest and creativity of the students. Henceforth, students lack a clear understanding of concepts. However, art integrated learning is a pedagogy that develops cross-cutting understanding, makes learning joyful and meaningful activity, and contributes to social and emotional development of the students. So a study was conducted to design an activity to teach physics through arts and to study the students‟ perspectives about art integration in physics. Henceforth, a descriptive survey research method was used to conduct the present study. A CBSE board school was selected conveniently from which 60 science stream higher secondary students were selected randomly from Lucknow City. A Likert-type scale was used to collect data. The results reveal that students liked the activities, found them engaging, motivating, and relevant to physics teaching. Some even regarded them to be waste of time. Additionally, the students also urged the need for the teacher's wisdom in designing and planning these activities as the teacher is the facilitator of the whole learning process in teaching through arts. This study may motivate the teachers to use this pedagogy as frequently as possible.